Does income inequality create excessive threats to the sustainable development of Russia? Evidence from intercountry comparisons via analysis of inequality heatmaps - Mikhail Dorofeev (Economies, 2021)
The paper explored the problem of income inequality in Russia in the context of the sustainable development of Russia. The research starts from the historical analysis of income inequality dynamics in Russia. Then, we discussed the problem of the inconsistency of data, comparing different sources (official data from the Rosstat database and alternative data from the World inequality database). The purpose of this research was to assess Russian specifics of income inequality and answer the question of if the income inequality in Russia is excessively high and needs extra government regulation in order to reach the trajectory of advanced sustainable development. To this end, we made intercountry comparisons and used the method of building income inequality heatmaps basing on a dataset from the World Inequality Database. Our sample includes the per-adult equivalent of household market income distribution in 27 developed and developing countries and world regions. The result of the research was that there are many countries in the world wherein the differentiation of income exceeds Russia's. Russian income inequality is lower than the world average, but the structure of the Russian household income distribution stands out by an extreme concentration of national income in the hands of the top 1%. We supported our results via the independent data from the Credit Suisse wealth inequality report, connecting a record level of wealth inequality in Russia with its problem of top 1% income inequality. It is recommended to gradually increase marginal tax rates on the income and wealth of the top 1% and continue developing an effective progressive tax system in Russia.
Keywords: 330; economic inequality; fiscal policy; government regulation; poverty; socio-economic policies; sustainable development; taxes